The coumarin osthole is a non-electrophilic agonist of TRPA1. (15th October 2022) - Torres, Karen V.; Pantke, Sebastian; Rudolf, Daniel; Eberhardt, Mirjam M.; Leffler, Andreas
Highlights: The antipruritic natural coumarin induces calcium-influx mainly in mouse DRG neurons expressing TRPA1. Osthole activates calcium-influx and inward currents in HEK 293 cells expressing human TRPA1. Osthole is a non-electrophilic TRPA1-agonist targeting the motif S873/T874. Abstract: The naturally occurring coumarin osthole has antipruritic properties, and recent reports suggest that this effect is due an inhibition or desensitization of the cation channels TRPV1 and TRPV3. Osthole was also suggested to activate TRPA1, an effect that should rather be pruritic than antipruritic. Here we characterized the effects of osthole on TRPA1 by means of ratiometric calcium imaging and patch clamp electrophysiology. In HEK 293 expressing human (h) TRPA1, osthole induced a concentration-dependent increase in intracellular calcium that was inhibited by the TRPA1-inhibitor A967079. In mouse dorsal root ganglion (DRG) cells, osthole induced a strong calcium-influx that was partly mediated by TRPA1. Osthole evoked fully reversible membrane currents in whole-cell as well as cell-free inside-out recordings on hTRPA1. Osthole failed to activate the mutant hTRPA1-S873V/T874L, a previously described binding site for the non-electrophilic TRPA1-agonists menthol and carvacrol. The combined application of osthole and carvacrol diminished channel activation, suggesting a competitive binding. Finally, osthole failed to activate TRPM8 and TRPV4 but induced a modest activation of hTRPV1 expressed in HEK 293 cells. We conclude that osthole is a potent non-electrophilic agonist of TRPA1. The relevance of this property for the antipruritic effects needs to be further explored.